Adenylate-cyclase VI transforms ventricular cardiomyocytes into biological pacemaker cells - Ruhparwar, Arjang; Kallenbach, Klaus; Klein, Gunnar; Bara, Christoph; Ghodsizad, Ali; Sigg, Daniel C.; Karck, Matthias; Haverich, Axel; Niehaus, Michael (Tissue engineering, 2010)
Introduction: When sinus node or atrioventricular (AV) node cells are damaged by disease, the implantation of an artificial cardiac pacemaker becomes necessary. In search for a biological alternative, the objective of this study was to demonstrate whether in vivo adenoviral gene transfer of Adenylate-Cyclase type VI (AC-VI) can create biological pacemaker activity in a porcine AV node block model. Genetic therapy of arrhythmic disorders of the heart has been subject of extensive studies. Cyclic AMP is generated in response to Beta-adrenergic receptor stimulation and also binds to HCN channels, where it regulates spontaneous rhythmic activity in the sinus node. - - Materials and Methods: Adenoviruses encoding either AC-VI or Beta-Galactosidase (lacZ) gene were injected into the lateral wall of the left ventricle of adult pigs via anterolateral thoracotomy at a dose of 1010 virus particles each. After 12 days, the AV node was ablated and three-dimensional electrophysiological cardiac mapping was performed using the Ensite™ electro-anatomical system. - - Results: After rapid ventricular pacing and administration of Isoprenalin, all animals of the AC-VI group exhibited an escape rhythm originating from the area of the left ventricular injection site at a rate of 100 + 7 beats/min (n = 5), whereas the escape rhythms in the control group (n = 4) originated from the right ventricle. Western blot analysis of the injection sites revealed significantly higher expression of AC-VI in the respective group as compared with the control group. - - Conclusions: Our study demonstrates that AC-VI gene transfer has the potential to create a biological pacemaker system.